2015
DOI: 10.1123/jpah.2012-0359
|View full text |Cite
|
Sign up to set email alerts
|

Walking to Work: The Roles of Neighborhood Walkability and Socioeconomic Deprivation

Abstract: Background:There are few studies that aimed to find a relationship between transportation-related physical activity and neighborhood socioeconomic condition using a composite deprivation index. The purpose of this study is to assess the relationship of neighborhood walkability and socioeconomic deprivation with percentage of adults walking to work. Methods: A walkability index and a socioeconomic deprivation index were created at block group-level. The outcome variable, percentage of adults who walk to work wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Prevalence of sufficient walking to improve health was 12-29% greater in high versus low walkable areas, and 1-8% greater in medium-high versus low walkable areas; no difference was observed between medium-low and low walkability areas. These results indicate that micro-level associations between walkability and walking manifest at macro-level spatial scales that are similar to those used for population health planning and intervention; support the validity of individual-level walkability evidence for informing population-level action to increase walking for health; and extends to middle and older aged populations, with previous research showing increased area-level walkability is associated with higher prevalence of walking in employed populations [ 12 , 17 , 34 ]. Our results also provide helpful information for targeting interventions to increase walking and walkability identified in the New South Wales State Government’s plan for growing Sydney [ 20 ].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Prevalence of sufficient walking to improve health was 12-29% greater in high versus low walkable areas, and 1-8% greater in medium-high versus low walkable areas; no difference was observed between medium-low and low walkability areas. These results indicate that micro-level associations between walkability and walking manifest at macro-level spatial scales that are similar to those used for population health planning and intervention; support the validity of individual-level walkability evidence for informing population-level action to increase walking for health; and extends to middle and older aged populations, with previous research showing increased area-level walkability is associated with higher prevalence of walking in employed populations [ 12 , 17 , 34 ]. Our results also provide helpful information for targeting interventions to increase walking and walkability identified in the New South Wales State Government’s plan for growing Sydney [ 20 ].…”
Section: Discussionsupporting
confidence: 68%
“…In our study this equated to median values of 46.0 residential dwellings per hectare, 162.5 intersections per square kilometer, and a land use entropy mix of 0.13. We have previously raised the possibility of a walkability threshold in the Sydney metropolitan region [ 17 ], and Kelly et al have recently reported macro-level journey to work results for North American populations consistent with a threshold effect [ 34 ]. However, we are unable to preclude the possibility that any threshold is due to scale effects, which can diminish associations as spatial granularity coarsens [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-SES populations are also less able financially to choose more PA-friendly alternatives such as living closer to work or in a safer and cleaner neighborhood, purchasing a gym membership, paying a fee to visit the community pool or recreation center, or purchasing services that afford time for PA such as housecleaning or childcare. 78,[104][105][106] As obesity becomes more prevalent in LMICs, and populations become more urban, it is important that future studies understand energy expenditure patterns and their relationship to obesity. suggest that a 70-minute-per-week difference in PA translates to walking 3 miles more per week given an approximate 20-minute-per-mile pace.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to develop a tailored intervention strategy for promoting active transportation to targeted groups, the importance of examining specific environmental factors related to context-specific behaviors has been emphasized by Giles-Corti et al [ 21 ]. In this context, an increasing number of studies have shown that environmental attributes, whether perceived or objectively measured, play crucial roles in specific transport-related behaviors [ 19 , 22 , 23 , 24 , 25 , 26 ]. Two previous reviews concluded that objectively-measured environmental attributes, such as higher population density, greater connectivity, and increased mixed land use, were consistently related to an increased amount of time spent walking and cycling for transportation [ 22 ]; the objectively-measured presence of cycling paths, short trip distances, proximity of cycling paths, and general traffic dangers were associated with cycling for transportation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%